THE EFFECT OF BIG BOOKS AS TEACHING MEDIA ON THE THIRD GRADE STUDENTS’ READING COMPREHENSION IN EAST BALI - ., I Putu Chandra Guna Krisna; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Ni Wayan Surya Mahayanti, S.Pd.,M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Ini merupakan sebuah penelitian eksperimental yang bertujuan untuk mengetahui apakah ada atau tidak perbedaan yang signifikan pada pemahaman membaca siswa kelas 3 SD Baruna Gianyar. Penelitian ini berbentuk Quasi Experimental of Posttest Only Control Group Study. Populasi yang digunakan adalah siswa kelas 3 di SD Baruna Gianyar. Terdapat dua kelas yang dipilih sebagai sampel. IIIA ditetapkan sebagai kelompok eksperimental dan mendapat Big Book sebagai teaching media sedangkan kelas IIIB ditetapkan sebagai kelompok control yang diajar menggunakan media conventional dalam proses belajar mengajar. Data yang diperoleh dianalisis t-test melalui SPSS 16.0. data hasil dari analisis menunjukan bahwa siswa yang diajar menggunakan Big Books sebagai teaching media memperoleh nilai rata-rata yang lebih baik dibandingkan dengan kelompok control. yang mana kelompok eksperimental memperoleh nilai rata-rata 83.8571 sedangkan kelompok control memperoleh nilai rata-rata 78.8571. Hasil dari t-test juga menunjukkan bahwa nilai dari t-observed (tobs) adalah 2.068 dan nilai dari t-critical value (tcv) adalah 1.7334 . Hal itu menunjukkan bahwa nilai dari tobs lebih tinngi dari nilai tcv. Oleh karena itu, dapat disimpulkan bahwa ada perbedaan yang signifikan pada pemahaman mebaca siswa kelas 3 antara siswa yang diajarkan menggunakan Big Books sebagai media dan siswa yang diajarkan menggunakan media konvensional.Kata Kunci : Big Book, media, pemahaman membaca, pembelajaran anak-anak. This is an experimental study that aims to investigate whether or not there is a significant difference in reading comprehension between students who are taught using Big Books as teaching media and thus who were taught using conventional media in grade 3 SD Baruna Gianyar. This quasi experimental study employed Posttest Only Control Group design. The population was taken from the third graders in Baruna Gianyar Elementary School. Two classes were selected as samples in this study class IIIA was designated as experimental group and got Big Books as teaching media while class IIIB was designated as a control group using conventional media in teaching and learning process. The data obtained were analyzed using t-test via SPSS 16.0. The result of the data analysis showed that the students who were taught using Big Books as teaching media gained better average score in comparison to the control group. The experimental was 83.8571 while the control group obtained the average score of 78.8571. The result of t-test also shows that the value of t-observed (tobs) is 2.068 and the value of t-critical value (tcv) is 1.7334. in other words the value of the tobs is higher than the value of tcv. Therefore, it can be concluded that there is a significant effect of the use of Big Books as teaching media on students’ reading comprehension at third grade of elementary school students in SD Baruna Gianyar.keyword : Big Book, Media, Reading Comprhension, teaching young learner.